2012
DOI: 10.1080/10934529.2012.689225
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of estrogens estrone, 17β-estradiol, estriol, 17α-ethinylestradiol, and diethylstilbestrol on sediment affected by different origins

Abstract: The sorption coefficients of estrone (E1), 17β-estradiol (E2), and estriol (E3), 17α-ethinylestradiol (EE2), and diethylstilbestrol (DES) on four sediments (BS1-4) collected downstream of agricultural, domestic, and industrial discharges were determined. The objective was to investigate the effect of sediment origin on the sorption affinity of natural and synthetic estrogens on sediments. Experimental results indicate that the sediment samples from different origins had differing estrogen sorption affinities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…For example, Lee et al (2003) reported log( K oc ) values for E2 that ranged from 3.21 to 3.46. This similarity in the sorption values lends support to the assumption that although degradates were present, they retained similar sorption properties compared with the parent compounds (Chen et al, 2012; Holthaus et al, 2002). Furthermore, as each experiment progressed, the sorption parameters increased in the same manner through time (Fig.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…For example, Lee et al (2003) reported log( K oc ) values for E2 that ranged from 3.21 to 3.46. This similarity in the sorption values lends support to the assumption that although degradates were present, they retained similar sorption properties compared with the parent compounds (Chen et al, 2012; Holthaus et al, 2002). Furthermore, as each experiment progressed, the sorption parameters increased in the same manner through time (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Aqueous concentrations (C; mole L −1 ) for [ 14 C]E2 and the [ 14 C]brominated‐E2 congeners were measured directly, and their sorbed concentrations (S; mole kg −1 ) were determined by difference for all time points; that is, radiochemical mass not measured in solution was assumed to be bound to the soil. Although the supporting data indicated that degradates had formed by Day 2 in the aqueous layer, other sorption studies for steroid estrogens reasonably assumed that degradates retain a steroidal structure and therefore possess similar physicochemical properties (e.g., water solubility) and soil sorption interactions as the parent estrogen (Chen et al, 2012; Holthaus et al, 2002). The sorption coefficients determined at earlier sample times should primarily reflect the parent estrogen.…”
Section: Methodsmentioning
confidence: 96%
“…The range of partition coefficients for E2 was based on a combination of previously determined parameters using experimental geochemical data derived from samples at the ASREC field site and soils from other agricultural sites (Mashtare, 2013). The range of partition coefficients for E1 was based on literature values as there was insufficient data from the ASREC field site (T. C. Chen et al., 2012; Gall et al., 2016). Given the significant uncertainty in estimating site‐specific rate constants, we used the range of partition coefficients for model calibration (Table 1), and the best fit parameter set was used in our simulation scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, significant correlations between logK oc (or logK d ) and logK ow values of the sex hormones have sometimes been suggested as evidence of hydrophobic partitioning interaction driving sorption (i.e., hydrophobicity-dominated sorption) (Zhang et al, 2011;Yang et al, 2019b;Yang et al, 2020c). For example, Chen et al (2012) found that the sorption magnitudes of 4 estrogens in soil-water systems were positively correlated with their logK ow values (R 2 > 0.92, p < 0.01). Yang et al (2020c) reported that the logK oc values of 7 progestins were significantly correlated with their logK ow values (logK oc = 0.30 logK ow + 1.91, R 2 = 0.70, p < 0.01).…”
Section: Logk Ow Valuesmentioning
confidence: 99%